Az interperszonális érzelemszabályozás és kötődés vizsgálata – első eredmények a saját érzelmek mások általi szabályozása és a bizonytalan kötődés vizsgálatában - NYITRAI, Erika (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2025)
Investigating Interpersonal Emotion Regulation and Attachment – Initial Findings on the Regulation of One’s Own Emotions by Others and on Insecure Attachment. Theoretical background: Despite the central role of emotion regulation, researchers have only recently begun to examine the interpersonal aspects of this process in adults. Aim: In this study, we sought to answer the question of what connections can be revealed between the regulation of one’s own emotions by others and insecure attachment. Methods: We collected data from 792 people in an online, cross-sectional questionnaire study between September and November 2023. The majority of the participants were middle-aged (34.58 years, standard deviation 11.97 years), living in a relationship, and predominantly men (46.5%) and women (53.5%) with higher education (61.4%). Measurement instruments: The study was conducted as part of a larger research project (ethical permit number: BTK/6890-1/2023). In this study, in addition to the Interpersonal Emotion Regulation (IERQ) questionnaire, attachment (ECR-R) and sociodemographic data were processed. Results: Similar to previous research, we found associations. The regulation of one’s negative emotions by others – reassurance, social modelling, and perspective taking – and the regulation of positive emotions by others were also associated with attachment anxiety. Among the regulation of one’s negative emotions by others, reassurance and the regulation of positive emotions by others showed a negative association with attachment avoidance. Conclusions: The examination of the relationship between the regulation of one’s emotions by others and attachment may be a priority area for future research, as it may help to clarify the adaptive and maladaptive roles of both.